Extra- and intracellular innate immune recognition in endothelial cells - Opitz, Bastian; Hippenstiel, Stefan; Eitel, Julia; Suttorp, Norbert (Thrombosis and Haemostasis, 2007)
The innate immune system represents the principal sensor of infections in multicellular organisms and might also mediate responses to some endogenous molecules. In this context, endothelial cells are among the first cells coming into contact with microbial or endogenous (danger-associated) molecules or whole pathogens entering the bloodstream. Since many bacteria and viruses invade the endothelium, endothelial cells are equipped with both extracellular and cytosolic surveillance systems capable of sensing microbial components, and endogenous danger-associated molecules. The receptor molecules, called pattern recognition receptors (PRRs), are classified as transmembrane or cytosolic molecules. While the transmembrane PRRs recognize extracellular and membrane-enclosed foreign organisms, the cytosolic PRRs appear to sense intracellular infections. Here we focus on both PRR classes in general, and outline the current knowledge of extra- and intracellular pattern recognition in endothelial cells and its potential role in vascular diseases and sepsis.
Keywords: Toll-like receptors; Nod-like receptors; CARD-helicases; endothelial cells